A prospective study on clinico-epidemiological profile and outcome in management of poisonous snake bite - Chaudhary, Mukesh Kumar; Gupta, Laxmi K.; Chand, Lokendra B.; Chaudhary, Ramesh; Ranpal, Sabin (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Snake bite is a major health problem in Nepal. According to WHO, annual morbidity due to snake bite is 162 out of 100,000 people in Nepal. Aim of the study is to observe epidemiology, clinical features, and analysis of possible relationship between time delay in administration of anti-snake venom (ASV) and mortality. Methods: This prospective observational study analyses the data of 81 patients admitted to the Lumbini zonal hospital, Butwal, Rupandehi, Nepal with history of snake bite between April to September, 2017. Results: In this study 56% patients were female. Patients of age group (15-30) years were maximum (38.27%). The study showed that 50.61% of snake bites were occurred outside home. Most of patients (84%) were from the Terai region. Average no. of vials used per case was (28±10) vials. Most of victims of snake bite were from rural areas. In most of cases we found that prothrombin time was prolonged. It was found that most of patients 57% reach hospital before 4 hours of snake bite. The mean days of hospital stay was 6±2.86. Most of case of snake bite was unknown (62%). The mortality rate in this study was 6.17%. Conclusions: There is a great need to improve in existing health care conditions for effective management of snake bite; it requires training of the personnel engaged in the emergency health care management, development of national guidelines based on the clinical trials, improving the distribution and easy availability of antivenom.